Adolescent Dating Behavior in the context of parental labor migration - Aji, Cyndu Indra; Handayani, Arri; Ismah, Ismah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Adolescent dating behavior is a social phenomenon influenced by various factors, one of which is the role of the family. This study aims to analyze the forms of adolescent dating behavior among those whose parents have migrated for work, the factors influencing such behavior, and the role of family, particularly migrant parents, in providing guidance and supervision. This research employs a qualitative approach using a case study method. Data were collected through interviews with adolescents whose parents have migrated, grandparents who serve as primary caregivers, and the parents themselves. The findings reveal that adolescents with migrant parents tend to have greater freedom in dating due to the lack of direct parental supervision and weak oversight from grandparents. The observed dating behaviors range from socially acceptable interactions to risky behaviors, such as physical contact that exceeds appropriate boundaries. The primary factors influencing adolescent dating behavior include internal drives, the influence of social media, and weak family control. Migrant parents often struggle with effective communication with their children, making it difficult to fully understand their dating patterns. Additionally, grandparents as primary caregivers tend to adopt a permissive parenting style, failing to enforce strict boundaries on adolescent dating behavior. This study contributes to the field of guidance and counseling by offering intervention strategies that can be implemented by counselors to address risky dating behavior among adolescents with migrant parents. Furthermore, it provides valuable insights for school counselors in designing effective intervention programs to support the social and emotional development of adolescents within the context of parental migration. and fostering better communication between adolescents, parents, and primary caregivers